Deciphering the suppressiveness of banana Fusarium wilt with organic residues - Heck, Daniel Winter [UNESP]; Ghini, Raquel; Bettiol, Wagner (Elsevier, 2019)
The use of organic residues in agriculture can contribute to the management of plant diseases and improvements in soil fertility. However, their effects on banana Fusarium wilt, caused by Fusarium oxysporum f. sp. cubense (Foc), are poorly understood. In this study, the biotic and abiotic effects on soil suppressiveness of banana Fusarium wilt were evaluated after incorporation of composted sewage sludge, biochar, shrimp peels and mussel shells into the soil. Residues were incorporated at rates of 0, 1, 2, 3, 4, and 5%, v:v in soil previously infested with Foc. Plantlets of banana cv. Maçã (AAB) were transplanted seven days after residue incorporation. Notable with respect to the other residues and concentrations studied, sewage sludge at 4% and 5% reduced plant disease (disease severity index and external severity) and increased plant growth. All concentrations of biochar and sewage sludge at 2% and 3% had intermediate effects. Disease severity and plant growth in plants grown in soil containing shrimp peels and mussel shells were similar to those of the untreated control. Negative correlations were observed between disease parameters and soil basal respiration, bacterial population, electrical conductivity, pH, V% (base saturation), CEC, P, K, Ca, Mg, Na, Zn, Mn and B.
Keywords: Biochar; Mussel shell; Panama disease; Sewage sludge; Shrimp peel; Suppressive soil